PENDUGAAN PLOIDI DAN KEKERABATAN BEBERAPA AKSESI PISANG HASIL KOLEKSI BALITBU TROPIKA SOLOK - Rinaldi, Riki; Mansyurdin, Mansyurdin; Hermanto, Catur (Sainstek : Jurnal Sains dan Teknologi, 2014)
The research on estimation ploidy and genetic relationships between sample collections from Solok Balitbu Tropic has been studied from Mei 2012 until November 2013. This study was done on experimental garden in Solok Balitbu Tropic and Genetic and Sitology Laboratory, Faculty of Math and Natural Science Andalas University. The aims of this study were to reveal the rate of ploidy on some bananas accession by using Stover and Simmonds (1987) scoring system and to relieve the rate of ploidy on some bananas accession based on quantity of chromosomes. The result revealed that the rate ploidy from 20 bananas accession the presence of 8 accessions of banana AA / AAA genome, AAB genome 8 accessions of banana and 4 banana accessions AB genome. Genetic relationship from dendrogram analysis showed that there were four groups bananas accession. Groups I, III, and IV were closely related toM. Acuminata, while group II related to M. balbisiana Key words : ploidy on some bananas accession genetic relationships